Local investments site selection and the behavior of the real estate market – case study in Poland - Siejka, Monika (International Conference “Environmental Engineering”, 2017)
One of the main tasks of real estate management in the area of the municipality is making decisions concerning the location of investments on a local scale. These decisions should be taken with the principle of sustainable development. For such an action obliges Poland's membership in the European Union. Poland as a member of the EU is obliged to implement the rules in force in the Member States. Bearing in mind that any investment impact directly or indirectly on the economic development of the municipality, is therefore a significant impact on the local real estate market. Investments that have a negative impact on the environment can contribute to a reduction in the activity of the local real estate market. While performing tasks related to the economic development of the region and the increase in quality of life, increases the activity of the local real estate market. The work was carried out research on the dynamics of changes in the local real estate market in the area of the municipality Skrzyszow in the Malopolska province in Poland, in connection with the construction of the reservoir.
Keywords: public investment; site selection; land management; real estate market; reservoir